Koncept fokusnega dogodka - Bauman, Sara (Družboslovne razprave, 2024)
In the article, we focus on operationalising the definition of an anthropogenic focusing event in the context of Slovenia. The concept of a focusing event was formulated by Kingdon (1984) and further developed by Birkland (1997, 2006). Both authors developed the concept for the USA, which differs from Slovenia in several important respects that can have a considerable impact on research that uses this concept in Slovenia. In the article, we reconstruct and operationalise the notion of a focusing event. The definition of the term is built according to the public policy definition of a focusing event (in Slovenian legislation) and how academics have defined such an event (Birkland, 1997). The result is a definition of an anthropogenic focusing event that is be precise and specific enough for guiding research in the area of Slovenia.
Keywords: antropogeni fokusni dogodki; definicije; fokusni dogodki; javne politike; nesreče; raziskovanje